Titanium carbonitride-based metal ceramic material and preparation method thereof

By covalently combining aluminum ions and calcium ions on the surface of titanium carbonitride, bimetal oxides are formed, and silicon carbide and aluminum nitride are combined. Ultrasonic dispersion technology and metal coordination are used to solve the problem of insufficient toughness of titanium carbonitride-based metal cermet materials, achieving high-density oxide film formation and mechanical properties optimization of the material, which is suitable for a wide range of applications in the field of cutting and manufacturing.

CN118685674BActive Publication Date: 2025-03-04YICHANG JOSN SEIKO TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410714203.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2025-03-04
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

The existing titanium carbonitride-based cermet materials have shortcomings in high toughness mechanical properties, resulting in limited applications in the field of cutting and manufacturing, especially in the processing of polymers, steels and advanced materials, where the materials have low toughness and are prone to cracks.

Method used

By covalently combining aluminum ions and calcium ions on the surface of titanium carbonitride, bimetal oxide is deposited through alkali treatment, and silicon carbide and aluminum nitride are combined. Through ultrasonic dispersion technology and metal coordination, a high-density oxide film is formed to improve the toughness and thermal conductivity of the material.

Benefits of technology

It significantly improves the toughness and mechanical properties of titanium carbonitride-based metal cermet materials, reduces the generation of cracks, extends the service life of the material, and reduces the cost, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004875073150000081
    Figure BDA0004875073150000081
  • Figure BDA0004875073150000091
    Figure BDA0004875073150000091
Patent Text Reader

Abstract

The invention discloses a titanium carbonitride-based cermet material and a preparation method thereof, and belongs to the technical field of metal ceramic composite material preparation. The titanium carbonitride-based cermet material comprises the following raw materials by weight: 50 to 60 parts by weight of bimetallic modified titanium carbonitride powder, 20 to 30 parts by weight of silicon carbide, 10 to 15 parts by weight of aluminum nitride and 5 to 10 parts by weight of metal bonding phase. The preparation method comprises: mixing bimetallic modified titanium carbonitride powder, silicon carbide, aluminum nitride and metal bonding phase, adding anhydrous ethanol, and sequentially wet grinding and drying to obtain a mixed powder; the mixed powder is pressed and formed, and then sent into a vacuum sintering furnace for sintering to obtain a titanium carbonitride-based cermet material. The invention covalently binds aluminum ions and calcium ions to the surface of titanium carbonitride through metal coordination, and then deposits aluminum ions and calcium ions on the surface of titanium carbonitride through alkali treatment, and forms bimetallic oxides through high-temperature calcination, thereby reducing costs while improving the toughness of titanium carbonitride-based cermets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of metal-ceramic composite materials, and in particular relates to a titanium carbonitride-based metal-ceramic material and a preparation method thereof. Background Art

[0002] Metal ceramics have the advantages of high hardness of ceramic materials and good elasticity and plasticity of metal materials. They also have good high temperature resistance and wear resistance, and have good application prospects in the manufacture of cutting tools. Compared with traditional cemented carbide metal materials, titanium carbonitride-based metal ceramics are widely used in cutting tools because of their high temperature red hardness and wear resistance, which can reduce the roughness of the machined surface and thus improve machining efficiency. However, with the development of industrialization, the demand for high-toughness mechanical properties is becoming more and more urgent. In the field of cutting manufacturing, metal ceramic tools are widely used in the processing of polymers, steels and advanced materials. However, due to the different physical properties between different phases, the interface stress in the organization increases, and the low toughness leads to the formation and expansion of cracks, which limits their application.

[0003] Patent 110616357B discloses a carbonitride-based metal ceramic and its preparation process. The invention improves the toughness of the metal ceramic material by introducing a multi-metal bonding phase and a hard phase for mixing; Patent CN112941389A discloses a titanium carbonitride-based metal ceramic and its preparation method and application. The invention introduces an organic aluminum source to increase the adhesion thickness of the powder on the surface of the material, and then introduces a second ceramic phase such as tungsten carbide and tantalum carbide to mix with it, thereby ensuring that while the thermal conductivity is improved, the mechanical properties of the titanium carbonitride-based metal ceramic material itself will not decrease; Patent CN111519115A discloses a high-toughness and high-wear-resistant titanium carbonitride-based metal ceramic material and its preparation method. The invention improves the toughness of the titanium carbonitride-based metal ceramic material by introducing a surface-modified carbon fiber material and combining it with a metal bonding phase powder and a carbide powder.

[0004] The above treatment methods all improve the toughness of the material itself by adding carbide powders such as tungsten carbide and tantalum carbide. Although this is very helpful in improving the toughness of the material, the high price of carbide powders such as tungsten carbide and tantalum carbide makes them unsuitable for large-scale application. Therefore, while improving the toughness and mechanical properties of titanium carbonitride-based cermets, the cost can be largely controlled, which has practical application value. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention covalently binds aluminum ions and calcium ions to the surface of titanium carbonitride through metal coordination, then deposits aluminum ions and calcium ions on the surface of titanium carbonitride through alkali treatment, and forms bimetallic oxides through high-temperature calcination to solve the problems raised in the background technology. Specifically, the technical solution of the present invention includes the following contents:

[0006] A titanium carbonitride-based metal ceramic material, the titanium carbonitride-based metal ceramic material comprising the following raw materials in parts by weight:

[0007] 50-60 parts by weight of bimetallic modified titanium carbonitride powder, 20-30 parts by weight of silicon carbide, 10-15 parts by weight of aluminum nitride and 5-10 parts by weight of metal bonding phase.

[0008] Furthermore, the preparation method of the bimetallic modified titanium carbonitride powder comprises the following steps:

[0009] The titanium carbonitride is dispersed in a mixed solution of aluminum nitrate and calcium nitrate by ultrasonic treatment and heated to 30° C. to 40° C. and stirred for 20 h to 24 h to form a mixed solution;

[0010] Add ammonia water dropwise to the mixed solution and stir until the pH value reaches 8-10, then filter to obtain a filter residue;

[0011] The filter residue is calcined at high temperature to obtain the bimetallic modified titanium carbonitride powder.

[0012] Furthermore, the ultrasonic treatment conditions include ultrasonic power of 300W to 400W and ultrasonic time of 10min to 20min.

[0013] Furthermore, the mass concentration of the mixed solution of aluminum nitrate and calcium nitrate is 50% to 70%, and the mass ratio of the aluminum nitrate to the calcium nitrate is 1:1.

[0014] Furthermore, the volume ratio of the titanium carbonitride: the mixed solution of aluminum nitrate and calcium nitrate is 1:50-100.

[0015] Furthermore, the high temperature calcination conditions include a calcination temperature of 600° C. to 700° C. and a calcination time of 4 h to 8 h.

[0016] Furthermore, the metal bonding phase is composed of iron powder and nickel powder of equal mass.

[0017] A method for preparing a titanium carbonitride-based metal ceramic material, the preparation method comprising the following steps:

[0018] The bimetallic modified titanium carbonitride powder, silicon carbide, aluminum nitride and metal bonding phase are mixed, and then anhydrous ethanol is added to perform wet grinding and drying in sequence to obtain a mixed powder;

[0019] The mixed powder is pressed and formed, and then sent into a vacuum sintering furnace for sintering to obtain the titanium carbonitride-based metal ceramic material.

[0020] Furthermore, the wet grinding conditions include a ball-to-material ratio of 8 to 10:1, a wet grinding speed of 200 r / min to 300 r / min and a wet grinding time of 20 h to 30 h.

[0021] Furthermore, the drying condition is vacuum drying at 100°C to 130°C for 8 to 10 hours.

[0022] Furthermore, the process parameters for the mixed powder pressing molding include a pressure of 250 to 300 MPa and a pressing time of 1 to 2 min.

[0023] Furthermore, the sintering parameters of the vacuum sintering furnace include a sintering temperature of 1400° C. to 1500° C., a sintering time of 40 min to 80 min, and a vacuum degree of 10 Pa to 20 Pa.

[0024] Compared with the prior art, the beneficial effects of the present invention include the following:

[0025] (1) The present invention pre-treats titanium carbonitride by first ultrasonically dispersing it in a mixed solution of aluminum nitrate and calcium nitrate, so that aluminum ions and calcium ions form covalent bonds with titanium carbonitride through metal coordination, and then directly alkali precipitates the treated titanium carbonitride to form metal hydroxide, and then calcines it at high temperature to obtain a bimetallic modified titanium carbonitride powder having a bimetallic oxide, and uses the metal oxide aluminum oxide to form a high-density oxide film on titanium carbonitride to reduce the appearance of pores in titanium carbonitride, so that the toughness of the titanium carbonitride-based metal ceramic material finally prepared is improved; because the use of aluminum ions alone may cause agglomeration, resulting in uneven distribution of the dense oxide film and poor performance improvement, the present invention also creatively uses ultrasonic dispersion technology for the pre-treatment dispersion of titanium carbonitride, and introduces a second metal ion calcium ion to produce coordination competition to weaken the generation of agglomeration, and the bimetallic ions and ultrasonic dispersion technology synergistically promote the generation and uniform distribution of the high-density oxide film, so that the finally obtained titanium carbonitride-based metal ceramic material has good toughness.

[0026] (2) The present invention also improves the thermal conductivity of the titanium carbonitride-based metal ceramic material by introducing silicon carbide and aluminum nitride, thereby optimizing the mechanical properties of the titanium carbonitride-based metal ceramic material, further reducing the generation of cracks, and increasing the service life of the titanium carbonitride and metal ceramic material.

[0027] (3) The present invention utilizes the coordination effect formed by bimetallic ions to modify titanium carbonitride, which has the advantage of low cost compared to materials such as tungsten carbide and tantalum carbide used in the prior art. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0029] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0030] Titanium carbonitride was purchased from Hunan Huawei Jingcheng Materials Technology Co., Ltd.;

[0031] Silicon carbide is purchased from Beijing Tianke Heda Semiconductor Co., Ltd.;

[0032] Aluminum nitride is purchased from Xiamen Juci Technology Co., Ltd.;

[0033] Iron powder and nickel powder were purchased from Fujia Technology Co., Ltd.

[0034] Preparation Example 1:

[0035] The preparation method of bimetallic modified titanium carbonitride powder specifically includes the following steps:

[0036] 250 g of aluminum nitrate nonahydrate and 250 g of calcium nitrate nonahydrate are mixed, purified water is added to dissolve, and then the volume is adjusted to 1 L to obtain a mixed solution of aluminum nitrate and calcium nitrate, and then titanium carbonitride is weighed according to 1% of the volume of the mixed solution and added to the mixed solution, and placed in an ultrasonic cleaning machine, the power of the ultrasonic cleaning machine is adjusted to 300 W, and then after ultrasonic treatment for 10 minutes, the mixed solution after ultrasonication is heated to 30° C. and stirred for 20 hours to obtain a mixed solution;

[0037] Ammonia water is added dropwise to the mixed solution while stirring until the pH value of the mixed solution is in the range of 8 to 10, then the addition of ammonia water is stopped, and the mixed solution is filtered through a vacuum filter to collect the filter residue, which is repeatedly rinsed with deionized water for 3 to 4 times and then vacuum dried to remove moisture, and the dried filter residue is placed in a crucible, heated to 600°C and treated for 4 hours to obtain a bimetallic modified titanium carbonitride powder.

[0038] Preparation Example 2:

[0039] The preparation method of bimetallic modified titanium carbonitride powder specifically includes the following steps:

[0040] 300 g of aluminum nitrate nonahydrate and 300 g of calcium nitrate nonahydrate are mixed, purified water is added to dissolve, and then the volume is fixed to 1 L to obtain a mixed solution of aluminum nitrate and calcium nitrate, and then titanium carbonitride is weighed according to 2% of the volume of the mixed solution and added to the mixed solution, and placed in an ultrasonic cleaning machine, the power of the ultrasonic cleaning machine is adjusted to 350 W, and then after ultrasonic treatment for 15 minutes, the mixed solution after ultrasonication is heated to 35° C. and stirred for 22 hours to obtain a mixed solution;

[0041] Ammonia water is added dropwise to the mixed solution while stirring until the pH value of the mixed solution is in the range of 8 to 10, then the addition of ammonia water is stopped, and the mixed solution is filtered through a vacuum filter to collect the filter residue, which is repeatedly rinsed with deionized water for 3 to 4 times and then vacuum dried to remove moisture, and the dried filter residue is placed in a crucible, heated to 650°C, and then treated for 6 hours to obtain a bimetallic modified titanium carbonitride powder.

[0042] Preparation Example 3:

[0043] The preparation method of bimetallic modified titanium carbonitride powder specifically includes the following steps:

[0044] 350 g of aluminum nitrate nonahydrate and 350 g of calcium nitrate nonahydrate are mixed, purified water is added to dissolve, and then the volume is fixed to 1 L to obtain a mixed solution of aluminum nitrate and calcium nitrate, and then titanium carbonitride is weighed according to 2% of the volume of the mixed solution and added to the mixed solution, and placed in an ultrasonic cleaning machine, the power of the ultrasonic cleaning machine is adjusted to 400 W, and then after ultrasonic treatment for 20 minutes, the mixed solution after ultrasonication is heated to 40° C. and stirred for 24 hours to obtain a mixed solution;

[0045] Ammonia water is added dropwise to the mixed solution while stirring until the pH value of the mixed solution is in the range of 8 to 10, then the addition of ammonia water is stopped, and the mixed solution is filtered through a vacuum filter to collect the filter residue, which is repeatedly rinsed with deionized water for 3 to 4 times and then vacuum dried to remove moisture, and the dried filter residue is placed in a crucible, heated to 700°C and treated for 8 hours to obtain a bimetallic modified titanium carbonitride powder.

[0046] Embodiment 1:

[0047] A method for preparing a titanium carbonitride-based metal ceramic material specifically comprises the following steps:

[0048] 50 parts by weight of the bimetallic modified titanium carbonitride powder of Preparation Example 1, 20 parts by weight of silicon carbide, 10 parts by weight of aluminum nitride and 5 parts by weight of a metal bonding phase (mixed with equal weights of iron powder and nickel powder) are mixed together in a ball mill and anhydrous ethanol is added. Carbide balls are added to the ball mill according to a ball-to-material ratio of 8:1. The rotation speed is controlled at 200 r / min and the ball milling is performed for 20 hours. After the ball milling is completed, the mixture is taken out and placed in a glass dish. The glass dish is then placed in a vacuum drying oven and dried at 100° C. for 8 hours to obtain a mixed powder.

[0049] The mixed powder is poured into a metal mold and pressed at a pressure of 250 MPa for 2 minutes. After the pressing, it is sent to a vacuum sintering furnace. The vacuum degree of the furnace is controlled to be 10 Pa. The vacuum sintering furnace is heated to 1400°C at 25°C / min, treated for 40 minutes, and naturally cooled to obtain titanium carbonitride and metal ceramic materials.

[0050] Embodiment 2:

[0051] A method for preparing a titanium carbonitride-based metal ceramic material specifically comprises the following steps:

[0052] 55 parts by weight of the bimetallic modified titanium carbonitride powder of Preparation Example 2, 25 parts by weight of silicon carbide, 12 parts by weight of aluminum nitride and 7 parts by weight of a metal bonding phase (mixed with equal weights of iron powder and nickel powder) were mixed together in a ball mill and anhydrous ethanol was added. Carbide balls were added to the ball mill according to a ball-to-material ratio of 9:1. The rotation speed was controlled at 250 r / min and the ball milling was performed for 25 hours. After the ball milling was completed, the mixture was taken out and placed in a glass dish. The glass dish was then placed in a vacuum drying oven and dried at 120° C. for 9 hours to obtain a mixed powder.

[0053] The mixed powder is poured into a metal mold and pressed at a pressure of 300 MPa for 1 min. After the pressing, it is sent to a vacuum sintering furnace. The vacuum degree of the furnace is controlled to be 15 Pa. The vacuum sintering furnace is heated to 1450°C at 25°C / min, treated for 60 min, and naturally cooled to obtain titanium carbonitride and metal ceramic materials.

[0054] Embodiment 3:

[0055] A method for preparing a titanium carbonitride-based metal ceramic material specifically comprises the following steps:

[0056] 60 parts by weight of the bimetallic modified titanium carbonitride powder of Preparation Example 3, 30 parts by weight of silicon carbide, 15 parts by weight of aluminum nitride and 10 parts by weight of a metal bonding phase (mixed with equal weights of iron powder and nickel powder) were mixed together in a ball mill and anhydrous ethanol was added. Carbide balls were added to the ball mill according to a ball-to-material ratio of 10:1. The rotation speed was controlled to 300 r / min and the ball milling was performed for 30 hours. After the ball milling was completed, the mixture was taken out and placed in a glass dish. The glass dish was then placed in a vacuum drying oven and dried at 130° C. for 10 hours to obtain a mixed powder.

[0057] The mixed powder is poured into a metal mold and pressed at a pressure of 300 MPa for 2 minutes. After the pressing, it is sent to a vacuum sintering furnace, the vacuum degree of the furnace is controlled to be 20 Pa, the vacuum sintering furnace is heated to 1500°C at 25°C / min, treated for 80 minutes, and naturally cooled to obtain titanium carbonitride and metal ceramic materials.

[0058] Comparative Example 1:

[0059] Preparation of modified titanium carbonitride powder:

[0060] The calcium nitrate in Preparation Example 1 was removed, and the 250 g of aluminum nitrate nonahydrate in Preparation Example 1 was increased by 500 g, and the rest was the same as Preparation Example 1;

[0061] Preparation of titanium carbonitride-based cermet materials:

[0062] The bimetallic modified titanium carbonitride powder in Example 1 was replaced by the modified titanium carbonitride powder in Comparative Example 1, and the rest was the same as in Example 1.

[0063] Comparative Example 2:

[0064] Preparation of bimetallic modified titanium carbonitride powder:

[0065] The ammonia water in Preparation Example 2 was replaced with a sodium hydroxide solution with a mass concentration of 40% to adjust the pH, and the other conditions were kept the same as those in Preparation Example 2;

[0066] Preparation of titanium carbonitride-based cermet materials:

[0067] The bimetallic modified titanium carbonitride powder in Example 2 was replaced by the bimetallic modified titanium carbonitride powder in Comparative Example 2, and the rest was the same as in Example 2.

[0068] Comparative Example 3:

[0069] The silicon carbide and aluminum nitride in Example 3 are removed, and the rest are the same as in Example 3.

[0070] Comparative Example 4:

[0071] The anhydrous ethanol in Example 3 was replaced with a mixed solution of water and ethanol of equal mass, and the rest was consistent with Example 3.

[0072] Comparative Example 5:

[0073] The bimetallic modified titanium carbonitride powder in Example 3 was directly replaced with titanium carbonitride, and the rest was consistent with Example 3.

[0074] The performance of the titanium carbonitride-based cermet materials obtained in Examples 1 to 3 and Comparative Examples 1 to 5 was tested, and the results are shown in the following table:

[0075]

[0076]

[0077] From the above table we can see that:

[0078] (1) In Comparative Example 1, aluminum nitrate alone was used for coordination and alkali precipitation to obtain a single aluminum oxide film. Due to the agglomeration of aluminum oxide, the film was unevenly distributed, resulting in a decrease in mechanical properties compared with Example 1, and fine cracks were generated on the surface of the material;

[0079] (2) In comparative example 2, inorganic strong alkali sodium hydroxide was used for alkali precipitation to prepare the oxide film. However, since the sodium ions of inorganic strong alkali sodium hydroxide also have a coordination effect, they may further competitively combine with the aluminum ions and calcium ions used for modification, resulting in a decrease in mechanical properties compared with Example 2.

[0080] (3) In comparative example 3, silicon carbide and aluminum nitride are not used, and the thermal conductivity of the material decreases sharply, which has a significant impact on the mechanical properties;

[0081] (4) The medium used for wet grinding in Comparative Example 4 contained water, which caused the aluminum nitride to hydrolyze and the mechanical properties to decrease.

[0082] (5) In Comparative Example 5, titanium carbonitride is directly used to prepare titanium carbonitride-based metal ceramic material, and the mechanical properties are significantly reduced.

[0083] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A titanium carbonitride-based cermet material, characterized in that: The titanium carbonitride-based metal ceramic material comprises the following raw materials in parts by weight: 50-60 parts by weight of bimetallic modified titanium carbonitride powder, 20-30 parts by weight of silicon carbide, 10-15 parts by weight of aluminum nitride and 5-10 parts by weight of a metal bonding phase; The preparation method of the bimetallic modified titanium carbonitride powder comprises the following steps: The titanium carbonitride is dispersed in a mixed solution of aluminum nitrate and calcium nitrate by ultrasonic treatment and heated to 30° C. to 40° C. and stirred for 20 h to 24 h to form a mixed solution; Add ammonia water dropwise to the mixed solution and stir until the pH value reaches 8-10, then filter to obtain a filter residue; The filter residue is calcined at high temperature to obtain the bimetallic modified titanium carbonitride powder; The mass concentration of the mixed solution of aluminum nitrate and calcium nitrate is 50% to 70%, and the mass ratio of the aluminum nitrate to the calcium nitrate is 1:

1.

2. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The ultrasonic treatment conditions include ultrasonic power of 300W to 400W and ultrasonic time of 10min to 20min.

3. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The volume ratio of the titanium carbonitride: the aluminum nitrate and calcium nitrate mixed solution is 1:50-100.

4. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The high temperature calcination conditions include a calcination temperature of 600° C. to 700° C. and a calcination time of 4 h to 8 h.

5. The titanium carbonitride-based metal ceramic material according to claim 1, characterized in that: The metal bonding phase is composed of iron powder and nickel powder of equal mass.

6. A method for preparing a titanium carbonitride-based metal ceramic material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: The bimetallic modified titanium carbonitride powder, silicon carbide, aluminum nitride and metal bonding phase are mixed, and then anhydrous ethanol is added to perform wet grinding and drying in sequence to obtain a mixed powder; The mixed powder is pressed and formed, and then sent into a vacuum sintering furnace for sintering to obtain the titanium carbonitride-based metal ceramic material.

7. The method for preparing a titanium carbonitride-based metal ceramic material according to claim 6, characterized in that: The wet grinding conditions include a ball-to-material ratio of 8 to 10:1, a wet grinding speed of 200 to 300 r / min and a wet grinding time of 20 to 30 hours.

8. The method for preparing a titanium carbonitride-based metal ceramic material according to claim 6, characterized in that: The sintering parameters of the vacuum sintering furnace include a sintering temperature of 1400° C. to 1500° C., a sintering time of 40 min to 80 min, and a vacuum degree of 10 Pa to 20 Pa.

Citation Information

Patent Citations

  • Titanium-carbonitride-based composite metal ceramic material microwave sintering process

    CN110373593A

  • Ti(C,N) based metal ceramic nitrogen atmosphere sintering process

    CN111195724A